1997
DOI: 10.1093/ajcn/65.1.149
|View full text |Cite
|
Sign up to set email alerts
|

Cryptosporidium infection in infancy as a cause of malnutrition: a community study from Guinea-Bissau, west Africa

Abstract: Cryptosporidium parvum causes persistent diarrhea in young children in developing countries. To determine the interaction between nutritional status and cryptosporidiosis, an open cohort of 1064 children younger than 3 y of age was followed for 1441 child-years by weekly diarrhea recall visits. A total of 5072 weight and 4264 height measurements was made. There were no tendencies of low weight (P = 0.38) or height (P = 0.16) in children who acquired cryptosporidiosis. Cryptosporidiosis in infancy was accompani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
92
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(97 citation statements)
references
References 16 publications
2
92
0
Order By: Relevance
“…However, this finding is biologically plausible and supports previous studies that have shown deleterious effects on growth and development after symptomatic and asymptomatic infections 4 in children who acquired the infection at less than one year of age and with boys rather than girls affected more significantly. 4,28,32 In a longitudinal study from Brazil, C. hominis and C. parvum infections were associated with decrease in HAZ scores within three months postinfection but this decrease was found to persist at 3-6 months after C. hominis infections, but not C. parvum infections. 35 Low birth weight, malnutrition, stunting and lack of breastfeeding have been reported to predispose children to cryptosporidiosis.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, this finding is biologically plausible and supports previous studies that have shown deleterious effects on growth and development after symptomatic and asymptomatic infections 4 in children who acquired the infection at less than one year of age and with boys rather than girls affected more significantly. 4,28,32 In a longitudinal study from Brazil, C. hominis and C. parvum infections were associated with decrease in HAZ scores within three months postinfection but this decrease was found to persist at 3-6 months after C. hominis infections, but not C. parvum infections. 35 Low birth weight, malnutrition, stunting and lack of breastfeeding have been reported to predispose children to cryptosporidiosis.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, a longitudinal study from Peru consistently identified more asymptomatic infections than symptomatic infections. 4,27,29 Both longitudinal studies from Brazil and Israel and those from Guinea-Bissau 32 and Uganda 2 identified more persistent (diarrhea lasting ≥ 14 days) diarrhea than acute diarrhea (diarrhea lasting less than 4 days). However, no persistent diarrhea was found in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the Mexican survey also estimated a prevalence of undernutrition for ZH/A of 8.9% in [21]. Some years before Molbak et al [22] found that Cryptosporidium infection was associated with the highest weight loss for children (both boys and girls) who contracted cryptosporidiosis before reaching one year of age. In addition, the proportion of children at risk for undernutrition was relatively high in this study.…”
Section: Discussionmentioning
confidence: 99%
“…is not restricted to immunocompromised hosts, it is also found in immunocompetent individuals (Nchito et al 1998;Gatei et al 2006;Salyer et al 2012). This parasite frequently infects children, in which it may have adverse effects on nutritional outcomes, affecting intestinal absorption, nutrition, and childhood development (Checkley et al 1997;Mondal et al 2009;Mølbak et al 1997). Data on asymptomatic individual carriage are scarce although C. spp.…”
Section: Introductionmentioning
confidence: 99%